2011
DOI: 10.1007/s10086-011-1189-7
|View full text |Cite
|
Sign up to set email alerts
|

Radial variations of vibrational properties of three tropical woods

Abstract: Radial trends of vibrational properties, including the specific dynamic modulus (E'/ρ) and damping coefficient (tanδ), were investigated for 3 tropical rainforest hardwood species, Simarouba amara, Carapa procera and Symphonia globulifera by free-free flexural vibration test. The microfibril angle (MFA) was estimated through X-Ray diffraction. Consistent patterns of radial variations were observed for all studied properties. E'/ρ was found to decrease from pith to bark, which is strongly related to the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
0
2
0
4
Order By: Relevance
“…Hardwoods are generally known to have relatively small variation in MFA within and between species as compared to softwoods (Donaldson 2008). Zhang et al (2011) reported a very similar MFA in low density Simarouba amara and high density Symphonia globulifera. They also reported that the specific dynamic modulus is highly correlated with the microfibril angle in wood.…”
Section: Resultsmentioning
confidence: 99%
“…Hardwoods are generally known to have relatively small variation in MFA within and between species as compared to softwoods (Donaldson 2008). Zhang et al (2011) reported a very similar MFA in low density Simarouba amara and high density Symphonia globulifera. They also reported that the specific dynamic modulus is highly correlated with the microfibril angle in wood.…”
Section: Resultsmentioning
confidence: 99%
“…Esta diversidad puede explicarse por la variabilidad natural en la magnitud de las características físicas que existe entre especies y al interior de una especie (Perré, Almeida, Ayouz y Frank 2016), por la heterogeneidad anatómica (Schubert, Gsell, Dual, Motavalli y Niemz, 2009), por la anisotropía material (Brémaud et al 2011) y por la higroscopicidad del tejido leñoso (Mvondo, Meukam, Jeong, Meneses y Nkeng 2017). La diversidad en las propiedades físico-mecánicas de la madera también depende tanto de factores genéticos como ambientales y se encuentra en todos los niveles de gimnospermas y angiospermas, entre árboles de climas tropicales y templados, entre poblaciones de una especie determinada, entre árboles de una población y, finalmente, en ubicaciones de muestreo dentro de un solo árbol (Zhang et al 2011).…”
Section: Madera Laminadaunclassified
“…En général, la tendance est liée à la densité du bois près de la moelle appelée densité initiale. La densité du bois est supposée augmenter pour les bois à densité initiale faible, comme c'est le cas chez l'okoumé, et baisser dans les bois à densité initiale forte, comme c'est le cas chez le kevazingo (Lehnebach, 2015 ;Plourde et al, 2015 ;Lehnebach et al, 2019 sur la variation radiale de l'AMF et de l'angle du fil chez les espèces tropicales (Zhang et al, 2011 ;Bossu et al, 2018). Alors que, chez les résineux des climats tempérés, on observe typiquement une baisse d'AMF suivant la distance à la moelle, attribuée en général à un besoin de flexibilité dans le jeune âge qui disparaît une fois que le diamètre de l'arbre est assez important et donc le tronc plus rigide (Burdon et Cown, 2004 ;Clark et al, 2006 ;Moore et al, 2014), chez certaines espèces tropicales, on observe plutôt une augmentation de l'AMF en partant de la moelle vers l'écorce (Zhang et al, 2011).…”
Section: Angle Des Microfibrilles (°)unclassified